Avaliação da influência do acoplamento de risers no movimento de jogo de um FPSO - Diezel, Alexandre Rezende (2017)
This work presents a comparison between the coupled and uncoupled formulations for computational simulation and analysis of the roll motions of an FPSO attached to a set of flexible risers in a deep-water scenario. The evaluation of the motions of the hull and the structural dynamic behavior of the subsea lines are usually made in different steps of the design, so that the dynamic interaction between the two physical domains is rarely considered. Descriptions of the analysis methodologies and the theories associated to the physical phenomena are included. In this study, a set of simulations using regular and irregular waves were performed to quantify this interaction. Besides the variation in the roll motions due to the coupling effects, the influence in the top tensions of a few selected risers is also investigated. The results show significant reductions in both parameters studied, leading to the conclusion that coupling effects can be relevant to the riser design.